1991
DOI: 10.1530/acta.0.1240497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging and sex on plasma insulin-like growth factor I (IGF-I) levels in normal adults

Abstract: Effects of aging and sex on total plasma IGF-I levels were studied in 207 normal adults (103 males and 104 females), aged 21 to 80 years. Plasma IGF-I concentrations were measured by specific radioimmunoassay after extraction with acid-ethanol. Plasma IGF-I levels ranged from 50.8 to 480.6 \ g=m\ g/ l with a mean (\m=+-\sd)value of 200.7\m=+-\81.9 \g=m\g/l in these normal adults. The mean plasma IGF-I levels were higher in females than in males in the second decade (332.6\m=+-\63.9 vs 252.4\m=+-\45.2\g=m\g/l,p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
1
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 21 publications
8
51
1
1
Order By: Relevance
“…However, in contrast to recently published studies, we found no significant gender differences in IGF1 levels in the middle-aged-and oldest-old subjects (37,38). Gender differences were present for IGFBP3 levels consistent with the findings of previous studies (39).…”
Section: Discussionsupporting
confidence: 73%
“…However, in contrast to recently published studies, we found no significant gender differences in IGF1 levels in the middle-aged-and oldest-old subjects (37,38). Gender differences were present for IGFBP3 levels consistent with the findings of previous studies (39).…”
Section: Discussionsupporting
confidence: 73%
“…The minimum detectable quantity was 5 IU/l. Plasma IGF-I levels were measured by speci®c RIA after acid± ethanol extraction as previously described (18). Plasma and urinary Cr were measured by an autoanalyzer (TBA50S, Toshiba, Tokyo, Japan).…”
Section: Assaysmentioning
confidence: 99%
“…Comparison tests of continuous variables were performed using an unpaired t-test or one-way ANOVA followed with Turkey's post hoc test. It is known that total IGF-I concentration declines with increased age in adults [22,23]. In the present study, all analyses regarding serum IGF-I levels were adjusted for age.…”
Section: Statistical Analysesmentioning
confidence: 97%